Tectonic control on great earthquake periodicity in south-central Chile - Diego Aedo; Daniel Melnick; Marco Cisternas; Dominik Brill (Communications Earth & Environment, 2024)
Abstract Multi-millennial records of great megathrust earthquakes have highlighted differences in periodicity and recurrence behavior. Understanding tectonic processes responsible for these differences is relevant for fault mechanics and hazard models. Here, we present a paleoseismic record inferred from raised beach ridges in the 2010 Maule earthquake (Mw 8.8) segment in south-central Chile that includes 24 interseismic intervals over 4.5 kyr suggesting a weakly-periodic recurrence behavior. In turn, great earthquakes in the adjacent 1960 Valdivia earthquake (Mw 9.5) segment occurred with periodic recurrence over the same time span. Both segments have similar trench sediments thicknesses as well as rheological and geometrical boundary conditions, but Maule has a wider frontal accretionary wedge and several splay faults rooted in the seismogenic zone whereas Valdivia lacks splay faults and trench sediments are mostly subducted and underplated. These differences may have an impact on upper-plate compliance and megathrust friction, affecting earthquake size and recurrence periodicity.